Identification and growth promotion effect of rhizosphere probiotics in kiwifruit (Bangladesh Journal of Botany, 2025)
This study assessed rhizosphere probiotics' isolation, identification, and growth-promoting effects in kiwifruit. Kiwifruit seedlings were collected from diverse fields and transported to the lab under sterile conditions. Rhizosphere soil was air-dried, weighed (1g), and serially diluted for bacterial isolation at 27°C for 48 hours. The isolates displayed circular, greenish-yellow colonies and were all Gram-negative. Biochemical tests showed catalase-positive reactions, with variable results for other tests. Dextrose fermentation was observed in all isolates. Among the seven (LPN1–LPN7), LPN5 exhibited strong antifungal activity against Fusarium solani, inhibiting 40% of its radial growth after eight days. All isolates produced indole-3-acetic acid (IAA), with LPN6 generating the highest levels. LPN5 demonstrated potential as a bio-inoculant due to its IAA production, phosphate solubilization, HCN, ammonia production, and biocontrol properties, making it promising for bio-fertilization and biological control in kiwifruit and other crops.Bangladesh J. Bot. 54(1): 67-74, 2025 (June)